Respon Anggota Klub Vespa Sidat Terhadap Kegiatan Khitobah Monologis - Azhari, Shofiyulloh (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2014)
This study aims to examine the response of Vespa SIDAT Club members to the monologic khitobah (religious speech) activities regularly conducted as a form of spiritual development within the community. Initially known as a street-based group with a negative public image, the Vespa SIDAT Club underwent social transformation through a community-based da’wah approach. The research employed a descriptive quantitative method, using observation, questionnaires, and documentation for data collection. Findings indicate that the monologic khitobah sessions were well-executed and positively received by club members. Participants showed high levels of attention, both spontaneous and intentional, with primary motivations including the desire to gain religious knowledge and general understanding. Acceptance of the preacher, content, and delivery method was notably strong, reflecting trust and active engagement. Although comprehension of the material was moderate, there were signs of internalization of Islamic values in members’ daily lives. The study concludes that monologic khitobah is an effective da’wah strategy for nurturing character and spirituality within street-based communities. Recommendations are offered to club organizers to enhance the quality of the sessions and to members to improve focus during activities for optimal spiritual development outcomes.